Children's emerging ability to discriminate L1-varieties. Issue 5 (October 2018) - Kaiser, Irmtraud; Kasberger, Gudrun
Children in Austria are exposed to a large amount of variation within the German language. Most children grow up with a local dialect, German standard language and 'intermediate' varieties summarized as 'Umgangssprache'. Using an ABX design, this study analyses when Austrian children are able to discriminate native varieties of their L1 German (standard German vs local dialect). The results show children's early ability to register differences and similarities on an across-speaker level when sentences are held constant (i.e. to discriminate translation equivalents in the two varieties) and a later, rather sudden emergence of more abstract categories of the varieties, which encompass different phonological and lexical variables and enable children to match sentences which also differ lexically. In sum, discrimination ability seems to be relatively stable and consistent at the age of 8/9. Other than age, the mother's educational background, language variation at home and the immediate sociolinguistic setting (urban/rural) predict children's discrimination performance.